2008
DOI: 10.1002/hyp.7155
|View full text |Cite
|
Sign up to set email alerts
|

Comparing alpine watershed attributes from LiDAR, Photogrammetric, and Contour‐based Digital Elevation Models

Abstract: Abstract:As part of an alpine hydrological study in the Canadian Rocky Mountains, three digital elevation model (DEM) data sets were obtained for the purpose of watershed characterization. The data sources were: (1) archived public access BC TRIM (Terrain Resource Information Management) 1 : 20 000 contour vectors; (2) stereo aerial photography DEM with a derived point spacing between 5 m and 20 m; (3) airborne LiDAR (light detection and ranging) with point spacing from 1 m to 4 m. GIS layers of terrain and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…Typical estimates of vertical RMS errors from airborne LiDAR data used in glaciological applications are below 0.2 m (e.g. Arnold et al, 2006;Hopkinson et al, 2009;Pope et al, 2013), which is not drastically different from the preliminary estimates shown here. Planimetric accuracies reported in the current study are also similar to those reported by Arnold et al (2006), and Hopkinson et al (2009), who both estimated XY accuracies as being between 0.3 m and 0.4 m. Furthermore, use of a metric camera might reduce some of the errors, and given the growing availability and shrinking size of these cameras, this is a logical next step for UAV payloads.…”
Section: Discussionmentioning
confidence: 42%
“…Typical estimates of vertical RMS errors from airborne LiDAR data used in glaciological applications are below 0.2 m (e.g. Arnold et al, 2006;Hopkinson et al, 2009;Pope et al, 2013), which is not drastically different from the preliminary estimates shown here. Planimetric accuracies reported in the current study are also similar to those reported by Arnold et al (2006), and Hopkinson et al (2009), who both estimated XY accuracies as being between 0.3 m and 0.4 m. Furthermore, use of a metric camera might reduce some of the errors, and given the growing availability and shrinking size of these cameras, this is a logical next step for UAV payloads.…”
Section: Discussionmentioning
confidence: 42%
“…Hopkinson, 2004;Avian and Bauer, 2006;Kerr and others, 2009;Kassalainen and others, 2011;Nield and others, 2013). From such data, DSMs and surface profiles can be retrieved at sub-centimetre horizontal and vertical resolution over intermediate (<200 m) scan distances.…”
Section: Photogrammetry and Glacier Surface Characterizationmentioning
confidence: 95%
“…6). These are believed to be spurious features and probably represent a product of the way in which topographic data are converted to raster data (Hopkinson et al, 2009). A possible way in which this problem will be avoided in future is discussed in Sect.…”
Section: Runoff Accumulation Demmentioning
confidence: 99%